Monitoring water quality using control charts at PDAM Surya Sembada Surabaya - Valeriana Lukitosari; Sunarsini Sunarsini; Wahyu Fistia Doctorina; Laksmi Prita Wardhani; Endah Rokhmati Merdika Putri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Statistical quality control using control charts is an easy-to-implement method to improve quality. Improvements in the quality of products and services are continuously implemented to meet consumer needs. Products and services must maintain the desired quality with as few defects as possible. Variations in products and services are naturally created to meet needs. Unintentional variation, but the cause can be found. Control charts can be used to monitor production; particularly serving as an early warning index of processes that are potentially out of control. To keep production under control, different control charts are prepared for different cases, created by combining upper and lower control limits. Points plotted on a graph can reveal certain patterns, which in turn allow the user to get specific information. Information on water production is very important in PDAM because water is the main product that meets the needs for the survival of humans, animals, plants, and various other needs. The supply of clean water that meets the requirements of quality standards is always pursued by PDAM Surya Sembada Surabaya. The Statistical control chart training will increase productivity and improve water quality, not only in terms of chemical, physical and biological quality. Good water quality will add value to the trust and community of PDAM.